2021
DOI: 10.1111/geb.13346
|View full text |Cite
|
Sign up to set email alerts
|

sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots

Abstract: Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 122 publications
0
51
0
1
Order By: Relevance
“…The values of alpha, beta, and gamma diversity used in this study to train the neural network models were derived from vegetation plot data (species inventories). We downloaded these data from the sPlotOpen database (Sabatini et al, 2021), only using plots where all vascular plants had been assessed. This resulted in a total of 7,896 vegetation plots for Australia (Fig.…”
Section: Vegetation Plot Datamentioning
confidence: 99%
See 3 more Smart Citations
“…The values of alpha, beta, and gamma diversity used in this study to train the neural network models were derived from vegetation plot data (species inventories). We downloaded these data from the sPlotOpen database (Sabatini et al, 2021), only using plots where all vascular plants had been assessed. This resulted in a total of 7,896 vegetation plots for Australia (Fig.…”
Section: Vegetation Plot Datamentioning
confidence: 99%
“…With the increasing availability of continental and global vegetation plot databases (Chytrý et al, 2016; Bruelheide et al, 2019; Sabatini et al, 2021), a new data source with extended spatial coverage has become widely available for the task of large-scale diversity estimation. Recently, Večeřa et al (2019) showed the potential of machine learning models (random forest models) to estimate the expected diversity for fixed size vegetation plots (alpha diversity), based on climatic and other predictors, when trained on alpha diversity data from vegetation plot databases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent decades, vegetation science has benefited from the development and maintenance of large vegetation databases (Dengler et al 2011). Historical vegetation relevés performed by early vegetation ecologists, together with recent vegetation plot data stemming from regional, but also national or continental research and survey projects, have been carefully assembled and digitally archived in the context of centralized initiatives (Chytrý et al 2016;Wiser 2016;Bruelheide et al 2019;Sabatini et al 2021). Such global collections of vegetation plot data are essential to investigate macroecological patterns and provide spatially meaningful answers to global issues, i.e.…”
Section: Introductionmentioning
confidence: 99%